Santri, Kopi dan Aktivitas Moderasi di Media Sosial - Dini Safitri (Program Pascasarjana Universitas Islam Negeri Sumatera utara, 2023)
Santri, coffee and moderation are words that can synergize. The habit of drinking coffee has become a mandatory tradition for students in Islamic boarding schools. This habit then gave rise to the phrase,